2013
DOI: 10.1007/s40258-013-0027-z
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden of Non-Cystic Fibrosis Bronchiectasis in the First Year after Diagnosis from A US Health Plan Perspective

Abstract: This study found that the cost of managing NCFB in the first year within a commercially enrolled population may be burdensome. Compared with previously published estimates in the literature, the burden of NCFB may be also increasing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 13 publications
2
52
0
Order By: Relevance
“…Despite this, bronchiectasis is associated with substantial socioeconomic cost due to the frequent use of primary and secondary health-care resources. An US epidemiological study of bronchiectasis-associated hospitalizations from 1993 to 2006 demonstrated an average annual hospitalization rate of 16.5/100 000 population with a significant annual increase of 2.4% in men and 3% in women (Seitz et al, 2010), with the cost of managing bronchiectasis appearing to be rising (Joish et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, bronchiectasis is associated with substantial socioeconomic cost due to the frequent use of primary and secondary health-care resources. An US epidemiological study of bronchiectasis-associated hospitalizations from 1993 to 2006 demonstrated an average annual hospitalization rate of 16.5/100 000 population with a significant annual increase of 2.4% in men and 3% in women (Seitz et al, 2010), with the cost of managing bronchiectasis appearing to be rising (Joish et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, antibiotics may be used as long-term therapy or for acute treatment of exacerbations. Along with the economic burden, the incidence of non-CF bronchiectasis continues to rise in the United States, with annual percentages increasing almost 9% every year from 2000 to 2007 (199,207). Although non-CF bronchiectasis is seen across the whole population, the prevalence appears to be highest in individuals of advanced age and females.…”
Section: Non-cf Bronchiectasismentioning
confidence: 99%
“…[4][5][6] The FACED score 7 was recently developed to classify patients' severity with a multidimensional scale, which includes age, degree of dyspnoea, FEV 1 %, presence of CBC by Pseudomonas aeruginosa (PA) and number of lobes affected. The few studies published to date on the costs associated with BE show that these are high, [8][9][10] and possibly greater than those described for chronic obstructive pulmonary disease (COPD). [11][12][13][14] Since most of the direct costs of the BE management can be attributed to exacerbations and baseline treatment, 15,16 it is reasonable to suppose that more severe patients give rise to higher health costs.…”
Section: Introductionmentioning
confidence: 97%